Medical error—the third leading cause of death in the US. (3rd May 2016) - Makary, Martin A; Daniel, Michael
Abstract : Medical error is not included on death certificates or in rankings of cause of death. Martin Makary and Michael Daniel assess its contribution to mortality and call for better reporting